Do producer prices cause consumer prices? - Mohd Fahmi Ghazali; Ooi Ai Yee; Mohd Zulkifli Muhammad (The Canadian Center of Science and Education, 2008)
The main purpose of this paper is to examine the relationship between consumer price index (CPI) and producer price index (PPI) in Malaysia. This research considers monthly data of consumer price index and producer price index from January 1986 to April 2007. The Johansen cointegration method suggests that there is long-run equilibrium relationship between these two variables. Both Engle Granger and Toda-Yamamoto causality tests find that there is uni-directional causality running from PPI to CPI.